Formula Organik Cair untuk Menambah Masa Tanam Semanggi di Lahan Kering - Budiwan, Adi; Kurniasari, Dwiyana Anela; Susanto, Heri (Proceedings Series on Physical & Formal Sciences, 2021)
Clover farmers in Semanggi Village, Community Unit 3 of Kendung Sememi, Surabaya, plant clover every year. Clover is a year-round plant. In the long dry season, it is very risky to die. With intensive watering treatment and organic fertilizer, it is expected to grow better and produce very high yields. A demonstration plot of clover land would provide innovation in optimal and eco-friendly clover cultivation. The method of activities in this training included lectures on understanding clover cultivation in dry land and how to provide the right fertilizer for clover. Preparation for Implementation, Preparation of Business Places, Demonstration of clover cultivation in dry land required a plot of land available with complete facilities. The tools needed were provided in the right amount so that the demonstration plot process was not complicated. The physical yield of clover, seen from the leaves, was quite satisfactory because the leaves were wide enough (quality) and would automatically increase the mass volume in terms of weight (quantity).